OPTIMALISASI LABORATORIUM KEUANGAN SYARI’AH DALAM MENINGKATKAN LITERASI SIVITAS AKADEMIKA TERHADAP PRODUK IKNB SYARI’AH - Aang Kunaifi (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2016)
The development of the Muslim community needs to the products of Shariah finance industry is a positive indication of the existence of shari'ah financial institutions. The phenomenon is not too surprising considering that the majority of the population in Indonesia is Muslim. Along with the increased understanding of the Shari'ah, the positive impact is people's desire to do business and take advantage of the products and services of financial institutions Shari'ah. But in fact there are still opinions in society, including in academic circles, about Shari'ah financial transaction system which is felt not much different from the conventional transaction system. The phenomenon indicates that literacy levels of society (including academics) are still not good. This study aimed to find the level of understanding and literacy of academicians of the IKNB Shari'ah products, and to know the expectations of society to the presence of IKNB Shari'ah. Based on the expectations of the community, shari'ah financial institutions can create its professionality by optimizing its the role itself. This research was conducted using qualitative methods to explore the opinions and expectations of society, especially the academicians. The strategy of the research is a phenomenal approach, involving all elements of academicians from the community with a heterogeneous geography and culture. The results showed that the level of literacy level academicians against IKNB shari’ah products stood at 62 on a scale of 100. It means that is enabled that the society have literacy levels below that figure. Of course this requires the efforts and support of the educational institutions to provide support to optimize all available resources. Based on the opinions and expectations of the community to discover, at least there are 10 steps to optimize the syari'ah financial laboratory to improve literacy of academicians of the IKNB Shari'ah products